The Portryal of Christianity in Achebe’s Arrow of God: A Postcolonial Perspective - Tatang Iskarna (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2020)
AbstractThe emergence of postcolonial criticism makes the voice of Africans’ colonial experience heard and seriously considered. In some ways, this voice is a little bit different from what the European poets or novelists have expressed in their literary texts. For most Europeans, colonialism is perceived as a civilizing force that benefits and progresses to the colonized African societies, primarily through one of its arms: Christianity. Although this religion, as most missionaries propose, has nothing to do with the worldly affair, such as a lust for natural resources and colony, it becomes an important cultural element to help the Europeans conquer the colonized African natives. During the era of colonialism, Christianity in Western discourse is perceived as a means of setting the African natives free from the barbaric traditional belief and savage way of life. Through Christianity, the colonized African natives are educated and taught to live a more modern and civilized life. However, some African writers at times give a different perspective on Christianity. This article explores how Christianity is portrayed through the characters and conflicts in Arrow of God (1964), a novel written by a Nigerian named Chinua Achebe. This portrayal can lead to a postcolonial discourse the novel intends to propose. Keywords: Christianity, colonialism, postcolonial criticism, postcolonial discourse Abstrak Munculnya kritik sastra poskolonial menjadikan suara yang mengekspresikan pengalaman kolonialisme dapat didengar dan sungguh-sungguh dapat diberi perhatian. Suara ini dalam beberapa hal agak eberbeda dengan apa yang disampaikan oleh novelis dan penyair Eropa dalam karya-karya mereka. Bagi kebanyakan orang Eropa, kolonialisme dipandang sebagai kekuatan pemberadaban yang dapat memberikan keuntungan dan kemajuan bagi masyarakat Afrika yang terjajah, terutama melalui salah satu tangan kanannya, yaitu agama Kristen. Meskipun agama ini tidak terkait dengan urusan nafsu dunia, seperti keinginan untuk menguasai sumber daya alam maupun tanah koloni seperti yang sering dikatakan oleh para misionaris, agama ini menjadi elemen penting untuk membantu kaum kolonial Eropa manaklukkan orang-orang pribumi Afrika. Selama masa kolonial, agama Kristen dalam wacana Barat dipandang sebagai media untuk membebaskan orangorang Afria dari kepercayaan tradisional yang barbar dan cara hidup yang tidak beradab. Melalui agama ini, orang-orang pribumi Afrika dididik dan diajar untuk menghidupi kehidupan yang lebih modern dan beradab. Namun demikian, beberapa sastrawan Afrika memberikan perspektif yang berbeda terhadap agama Kristen. Artikel ini akan mengeksplorasi bagaimana agama Kristen digambarkan melalui tokoh dan konflik dalam novel Arrow of God (1964) karya sastrawan Nigeria, Chinua Achebe. Gambaran ini akan menuntun pembaca pada wacana poskolonial yang dibangun oleh novel ini. Kata kunci: Agama Kristen, kolonialisme, kritik sastra poskolonial, wacana poskolonia